The Effect of Mode of Delivery and Duration of Labor on Subsequent Pregnancy Outcomes: A Retrospective Cohort Study. Issue 3 (24th September 2022) - Van Winsen, K.D.; Savvidou, M.D.; Steer, P.J.
Abstract : ( BJOG . 2021;128:2132–2139. [Epub August 30, 2021]) Gestational length of a pregnancy is varied with maternal age, medical conditions, race, and socioeconomic factors contributing. Highly correlated gestational length in subsequent pregnancies suggests that constitutional factors may also influence pregnancy outcomes. This study aimed to determine the method of delivery and labor duration of a first singleton labor on the subsequent pregnancy outcomes, including gestational length, method of delivery, and neonatal outcome.